Quality of service : the case of Telekom Malaysia Berhad, Kuching, Sarawak - Nancy, Rukem. (2002)
The paper detennines how customers of Telekom Malaysia Berhad (TMB) Kuching, Sarawak, critically rate the quality of services rendered to them via the Critical Incident Technique (CIT) and the SERVQUAL method. The study also identified components of the service delivery system that are most important in the customers' judgment) Questionnaires answered by 500 respondents that consistedof an even breakdown of business and residential customers of TMB Kuching revealed that TMB Kuching scored the highest in assurance followed closely by responsiveness and reliability. However, the overall mean scored for the above dimensions were way below the average mark measured on a five-point Likert scale. Mo t, if not all, the dimensions studied scored a below average point. The findings therefore indicated that customers found the quality of service to be poor. Despite the poor score, the findings can be used by managers of TMB Kuching to develop appropriate and professional service strategies customized to the needs of the customers.